Performance of Biomass and Exopolysaccharide Production from the Medicinal Mushroom Ganoderma lucidum in a New Fabricated Air-L-Shaped Bioreactor (ALSB) - Sugenendran Supramani; Nur Ardiyana Rejab; Zul Ilham; Rahayu Ahmad; Pau-Loke Show; Mohamad Faizal Ibrahim; Wan Abd Al Qadr Imad Wan-Mohtar (MDPI, 2024)
Indexed by WOS/Scopus/ERA